Leadership and management in early childhood: navigating contradictions and pedagogical practices to foster inclusivity - Manoharan Nalliah; Shorouk Aboudaher; Lim Wei Huan; Esayas Teshome Taddese (Institute of Advanced Engineering and Science, 2025)
Early years’ education is an important foundation for a child’s life-long learning, and leaders and managers in early childhood work settings have an important role in creating a nurturing environment that supports and enables children to learn regardless of their needs. This study investigates the challenges and contradictions leaders and managers face in early childhood education (ECE) settings. It examines how pedagogical praxis can be leveraged to foster inclusivity focusing on the tension between the intrinsic value of play and the pressure of child performativity meeting performance benchmarks. This qualitative study offers a constructive discussion on leadership practices in ECE and inclusion in Malaysia. The thematic analysis of nine interviews analyzed by N-VIVO software and showed the important considerations for enhancing leadership and management approaches, creating more inclusive spaces, and supporting the holistic development of early childhood curricula. The result offers a rich description of how leading practices are increasingly influenced by dominant trends in educational policies and society, including neoliberal agendas and narrowly conceived accountability systems that focus on measurable outcomes. It underlines the centrality of supporting the ongoing professional development of educators.